Panorama of EU regional programmes and projects : eastern partnership and Russia - Euroopan komissio (Publications Office of the European Union, 2013)
"The European Union is building an ever deeper relationship with Armenia, Azerbaijan, Belarus, Georgia, Moldova and Ukraine, supporting their reforms through the renewed European neighbourhood policy (ENP) and increasingly through one of the EU$1 (Bs newest external relations policies, the Eastern Partnership (EaP). With its biggest neighbour in the east, Russia, the EU has a separate strategic partnership. Each of these countries, except Belarus, has a partnership and cooperation agreement (PCA) that serves as a political and legal framework for cooperation. All of them are beneficiaries of the European neighbourhood and partnership instrument (ENPI), the financial tool that turns decisions taken on a political level into actions on the ground. Dialogue between the EU and its eastern neighbours is secured through joint institutions set up under the PCAs, the highest one being the Cooperation Council. With Russia, it is the Permanent Partnership Council." -- EU Bookshop.
Keywords: Social planning : Economic integration; Sustainable development : Economic integration; Democracy : Economic integration; European Union countries : Economic integration; kestävä kehitys; yhteiskuntakehitys; kansainvälinen yhteistyö; Azerbaijan; Ukraine; Armenia; Russia; Belarus; Georgia; Moldova; Venäjä; Euroopan unioni; Itä-Eurooppa